Rethinking Protection of Those Displaced by Humanitarian Crises - Martin, Susan F. (American Economic Review, 2016)
In June 2015, the UN High Commissioner for Refugees announced a landmark event in the history of his organization. UNHCR estimated that there were more refugees and displaced persons than it had counted since its establishment in 1950–almost 60 million who fled conflict and persecution. While certainly large in its own right, the number actually underestimates displacement in today's world. Many millions more are displaced each year and cumulatively from a much broader range of life-threatening humanitarian crises than captured by UNHCR's figures. An average of 26.4 million were displaced annually by acute natural hazards since 2008 and an unknown but sizeable number from gang and cartel violence, electoral and communal violence, nuclear and industrial accidents, and a range of other human made disasters. This paper argues for new legal, institutional and operational frameworks to more effectively address the situation of the totality of displaced persons.